Implicitation in Legal Translation - A Study of Spanish-Danish Translation of Judgments - Vesterager, Anja Krogsgaard (HERMES - Journal of Language and Communication in Business, 2016)
Whilst the concept of explicitation has spawned many research projects in the field of Translation Studies, implicitation remains an understudied area. This article addresses that research gap, reporting on the findings of an empirical study on Danish translators’ use of implicitations in their Spanish to Danish translations of an excerpt from a judgment. The aim of the study was to examine, on the one hand, whether the translators used implicitations in their translations, and, on the other hand, whether differences could be observed between experts and non-experts. The data reported here consisted of a Spanish source text and 10 translations into Danish by five experts and five non-experts. The translations were analysed using qualitative methods (consisting of contrastive text analysis) followed by a quantitative synthesis. Overall, the findings revealed that implicitations were very rare and, consequently, no conclusive results could be drawn in relation to translation expertise.